TEACHERS’ NEEDS AND READINESS FOR AI-ASSISTED AUGMENTED REALITY LEARNING MEDIA IN ELEMENTARY EDUCATION 5.0 - Dafit, Febrina; Ramadan, Zaka Hadikusuma; Efendi, Yoyon; Latif; Ansari, Khairil; Yusnadi (Seven Editora, 2026)
In the era of Education 5.0, teachers are required to integrate digital and intelligent technologies into their classroom practices. This study aims to analyze teachers’ needs and readiness for AI-assisted Augmented Reality (AR) learning media in elementary education by identifying their current use of learning models and media as well as the factors influencing their implementation. Using a descriptive survey design, data were collected from 67 fifth-grade teachers across 18 elementary schools in Pekanbaru through a Likert- scale questionnaire distributed via Google Forms. The findings reveal that while most teachers hold positive perceptions toward the use of learning models and media, their actual implementation remains limited. Factors such as teachers’ age, educational background, and technological competence were found to affect their readiness to adopt innovative media such as AI-assisted AR. These findings highlight the gap between pedagogical understanding and technological application, indicating the need for targeted training and professional development. The study provides empirical insights that can serve as a foundation for developing adaptive, AI-based AR learning environments that align with teachers identified needs and support meaningful learning in the context of Elementary Education 5.0. DOI: https://doi.org/10.56238/sevened2026.008-101